Some Insights Concerning the Halal Tourism Research. A Bibliometric Analysis - MAS’UD, Riduan; SYAMSURRIJAL, M. (Journal of Environmental Management and Tourism, 2022)
Halal tourism has become one of the topic issues that have a level of popularity among researchers in the scientific articles published in journals indexed in the Scopus database. This research study uses a bibliometric design analysis to map some insights related to the halal tourism by evaluating articles that have been published in journals indexed in Scopus database. Furthermore, data mining (knowledge discovery) techniques are used to analyze the titles and abstracts of 127 Scopus indexed journals that have been saved in the form of a CSV file. Finally, three analyzes are produced in this study: network visualization analysis, overlay visualization, and density visualization. This study's results indicate a significantly increased of articles on halal tourism, especially in the Islamic marketing journals. Also, the main outputs obtained though this bibliometric research related to the halal tourism, reveal which is the most popular authors, which is the most cited articles, which is the country with most publications, which is the research domain most approached. In the same manner is underline which is less approached practices, i.e. , halal tourism from the perspective of Islamic law, etc.